Expression of adhesins by some “Bordetella pertussis” strains isolated in Romania in different time periods - Georgeta Cristina OPREA; Veronica LAZĂR (Studia Universitatis Babeș-Bolyai. Biologia, 2018)
Bordetella pertussis is the etiological agent of whooping cough or pertussis, a respiratory infection in humans which can be prevented by vaccination. B. pertussis is characterized by a set of virulence factors involved in bacterial adherence to host-cells and consecutive colonization of the respiratory epithelium and in immunity too. In this study, we compared the expression of the specific adhesins with antigenic properties in some B. pertussis strains, including collection strains, vaccine strains and recently-isolated strains. The specific adhesins / surface antigens of B. pertussis are: a surface protein, named FHA (filamentous hemagglutinin) and fimbria Fim2 and Fim3. These antigens were evidenced using an indirect ELISA method, based on specific monoclonal antibodies binding to specific epitopes. The results showed that fimbrial antigens Fim3 are expressed by all new-isolated strains, compared to the older isolates, which expressed Fim2 or both Fim2, 3.